Infection and immunity - Davies, Huw, 1959- (Modules in life sciences., 1999)
Taking a disease-based approach, this text explores the interactions between pathogens and the human immune system and explains how mircoorganisms can evade the immune system and thus cause disease. Concise yet comprehensive.